2022 IEEE 95th Vehicular Technology Conference: (VTC2022-Spring) 2022
DOI: 10.1109/vtc2022-spring54318.2022.9860871
|View full text |Cite
|
Sign up to set email alerts
|

Parking Behaviour Analysis of Shared E-Bike Users Based on a Real-World Dataset - A Case Study in Dublin, Ireland

Abstract: In recent years, an increasing number of shared E-bikes have been rolling out rapidly in our cities. It therefore becomes important to understand new behaviour patterns of the cyclists in using these E-bikes as a foundation for the novel design of shared micromobility services as part of the realisation for next generation intelligent transportation systems. In this paper, we deeply investigate the users' behaviour of shared E-bikes in a case study by using the real-world dataset collected from the shared E-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As a result, promoting the uptake of ESMS has become strategically important for many European countries to achieve a sustainable and low-carbon transport system [5]- [8]. In Ireland, for instance, the government has established a clear pathway to step up the adoption of electric vehicles for transportation decarbonisation in the next decade with an ambitious target to reduce 51% of transport emissions by 2030 1 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, promoting the uptake of ESMS has become strategically important for many European countries to achieve a sustainable and low-carbon transport system [5]- [8]. In Ireland, for instance, the government has established a clear pathway to step up the adoption of electric vehicles for transportation decarbonisation in the next decade with an ambitious target to reduce 51% of transport emissions by 2030 1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, current ESMS suffer from critical design issues, such as lack of service integration and not being user-centric, which potentially significantly impedes mass adoption. In fact, some recent work has demonstrated that ESMS can create various burdens in modern traffic operation and management, including inappropriate parking challenges due to users' behaviours [1], charging issues due to lack of infrastructures [9], accessibility challenges due to lack of holistic planning and scheduling [10], as well as transaction challenges due to lack of speed and transparency [11], [12]. Typically, these challenges are dealt with either partially or individually without a holistic view of system-level design and optimization, with the result that one problem may be addressed for a given aspect but more problems can be created for others.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations